Cardiomyocyte-specific deletion of TLR4 attenuates angiotensin II-induced hypertension and cardiac remodeling - Theobald, Drew; Nair, Anand R.; Sriramula, Srinivas; Francis, Joseph (Frontiers in Cardiovascular Medicine, 2023)
Toll-like receptor 4 (TLR4) is an integral factor in the initiation of the innate immune response and plays an important role in cardiovascular diseases such as hypertension and myocardial infarction. Previous studies from our lab demonstrated that central TLR4 blockade reduced cardiac TLR4 expression, attenuated hypertension, and improved cardiac function. However, the contribution of cardiac specific TLR4 to the development of hypertension and cardiac remodeling is unknown. Therefore, we hypothesized that cardiomyocyte specific knockdown of TLR4 would have beneficial effects on hypertension, cardiac hypertrophy, and remodeling. To test this hypothesis, cardiomyocyte-specific TLR4 knockdown (cTLR4KO) mice were generated by crossing floxed TLR4 mice with Myh6-Cre mice, and subjected to angiotensin II (Ang II, 1 µg/kg/min or vehicle for 14 days) hypertension model. Blood pressure measurements using radio telemetry revealed no differences in baseline mean arterial pressure between control littermates and cTLR4KO mice (103 ± 2 vs. 105 ± 3 mmHg, p > 0.05). Ang II-induced hypertension (132 ± 2 vs. 151 ± 3 mmHg, p < 0.01) was attenuated and cardiac hypertrophy (heart/body weight; 4.7 vs. 5.8 mg/g, p < 0.01) was prevented in cTLR4KO mice when compared with control mice. In addition, the level of myocardial fibrosis was significantly reduced, and the cardiac function was improved in cTLR4KO mice infused with Ang II. Furthermore, cardiac inflammation, as evidenced by elevated gene expression of TNF, IL-6, and MCP-1 in the left ventricle, was attenuated in cTLR4KO mice infused with Ang II. Together, this data revealed a protective role for cardiomyocyte-specific deletion of TLR4 against Ang II-induced hypertension and cardiac dysfunction through inhibition of proinflammatory cytokines.